Pengembangan Kurikulum Muatan Lokal Seni Hadrah Pasuruan - Muhamad Mukhlason (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2016)
The development is aimed at generating Local Content Curriculum Hadrah Art in State Government Elementary School Mandaranrejo Pasuruan. The specific objective is the development of local curriculum is to enable students to know and be familiar with the cultural environment and to conserve and develop the art of Pasuruan tambourine. In the systematic development of local curriculum in the subjects of art tambourine local content, the development model used is Beauchamp's System Model. The result of the development of local curriculum is shaped tambourine arts curriculum documents that form the syllabus and lesson plans that have been validated by a judgment of the experts, the curriculum experts and subject matter experts with the aim to see the practical feasibility of the model used.